Development of Women's Role Values in the Batik Industry in Bakaran Pati Village 1977-1998 as a History Lesson - Ristiana, Nana (Universitas Negeri Semarang, 2017)
The research objectives: (1) knowing the work ethic of batik women in the village of Burnt Pati, (2) knowing the history of batik burnt Starch, (3) determining the role of women in the batik industry in the village of Burnt Pati years 1977-1998. The method in this study is based on historical research methods, namely (1) heuristics, (2) source criticism, (3) interpretation, and (4) historiography. Techniques to get the author done with the source observation, interviews, documentation, literature, and documentation studies. Based on the research conducted to obtain information, women have played an essential role in making batik since time immemorial. Batik is identical to the woman as the author. The development of Batik burnt also influences the amount of labor in women who work in the batik industry. The high work ethic of batik and batik will be profitable for the cottage industry, where they work among the many who love batik, making the women who have only worked as batik entrepreneurs turn to batik.